PERENCANAAN KOMUNIKASI GARDA PANGAN SEBAGAI ORGANISASI NON PROFIT DALAM MENJALIN KERJA SAMA DENGAN MITRA - Bagus Indra Setiawan; Mohammad Insan Romadhan (Sintesa, 2023)
Communication planning is crucial for a company/organization, not only do profit-oriented companies need communication plans, but non-profit companies such as Garda Pangan also need communication plans to establish cooperation with their partners. Garda Pangan, as a food bank since 2017, has consistently become a coordination center for potentially wasted surplus food to be distributed to underprivileged communities in Surabaya. Garda Pangan needs cooperation with partners with potentially wasted surplus food sources so that they are willing to alleviate the food waste problem together. Garda Pangan creates a communication plan to deliver messages to its audiences and partners effectively. This research aims to evaluate Garda Pangan in its communication planning to establish cooperation with partners. Researchers used descriptive qualitative research methods with data collection techniques using interviews, observation, and documentation. The theory used in this research is Philip Lesly's communication planning model, which has two main components: the organization that drives the activity and the public that is the target of the activity. The steps in the Organizational component that must be carried out are Analysis and Research,Policy Formulation, Implementation program planning, and Communication Activities. Meanwhile, for the Public component, there is Feedback and Evaluation. Garda Pangan uses two main components in its communication planning. Garda Pangan is the organization's first component, while the community and partners are the target public. Garda Pangan's communication planning has been carried out properly because all planning steps that have been made can be executed smoothly.